5-(4-hydroxy-3-dimethoxybenzylidene)-rhodanine (RD-1)-improved mitochondrial function prevents anxiety- and depressive-like states induced by chronic corticosterone injections in mice. (June 2016) - Yang, Nan; Ren, Zhili; Zheng, Ji; Feng, Lu; Li, Dongmei; Gao, Kai; Zhang, Lianfeng; Liu, Yanyong; Zuo, Pingping
Abstract: Most current pharmacologic antidepressant treatments target monoaminergic systems confronts some problems such as low rate of remission and high risk for relapse indicating new therapeutic strategy is urgently need. Evidences showed that impairments in mitochondrial function were associated with the pathogenesis of mood disorders and improvement in its function may be a novel therapeutic choice. In the present study, effects of 5-(4-hydroxy-3-dimethoxybenzylidene)-2-thioxo-4-thiazolidinone (RD-1) were investigated in mice model of depression/anxiety induced by corticosterone (20 mg/kg) subcutaneously repeated injections in 5-week male BALB/c mice. Our results showed that five weeks of corticosterone administration induced anxiety/depressive-like behavioral changes, including decreased central activities in open field test, increased the immobility time in forced swimming test and the latency in the novelty-suppressed feeding test, as well as reduced bodyweight. Results showed that oral administration with RD-1 at the doses of 25, 50, and 100 mg/kg for five weeks significantly improved the anxiety/depressive-like behavioral changes induced by corticosterone. In glucose metabolism analysis by photon emission computed tomography/-computed tomography (PET/CT) imaging, corticosterone significantly deactivated the prefrontal cortex (PFC), temporal lobe and hippocampus. RD-1 treatment obviously improved the energy metabolism in the involved brain regions. In primary cultured hippocampal neuron, corticosterone reduced speed of anterograde transport, yet speed of retrograde transport was increased. Furthermore, RD-1 enhanced the mitochondrial anterograde transport to supply energy for the neurotransmitter release. In conclusion, RD-1 prevents anxiety/depressive-like behavior of mice induced by corticosterone repeated injections with novel mechanism of improvement in the mitochondrial function. Highlights: RD-1 significantly improved anxiety/depressive-like behavior induced by corticosterone. RD-1 significantly improved the mitochondrial trafficking. RD-1 might be a promising candidate for depression treatment with a novel mechanism.